International cooperation and the case for multilateralism: an analysis from International law perspective - Hamid, Abdul Ghafur@Khin Maung Sein (2014)
Unilateralism and multilateralism both describe nations' foreign policy. They describe how nations interact with one another, but they have one key difference: the former describes one nation acting alone, while the latter describes a number of nations acting together. Both of these have different rationales behind them and different effects when they are used. In the age of globalization, international cultures and economies are intertwined in a variety of ways. Any action that a country takes, including actions that impact their internal economies, have an impact on other countries. Multilateralism has, therefore been increasingly accepted as the modus operandi in world politics. Over the last few decades, nations have come to realize that the challenges of security, peacekeeping, disease control, human rights violations, and pollution, among others, are too vast and complex for any nation or group of nations, no matter how powerful, to effectively manage on its own. Because of the truly global nature of these issues, the actions or inaction of every country affect the wellbeing of all countries and peoples, and no country is able to address these issues alone. Multilateralism is the answer to all these issues of global concern.